Carthamus Tınctorius L. (Safflower) extracts inhibit expression of metastatic genes of MDA-MB-231 breast cancer cells: Safflower extracts ınhıbıt breast cancer cell metastasıs - Kaçaroğlu, Demet; Kalaycıoğlu, Gökçe Dicle; Özden, Ayşe Kevser (Cellular and Molecular Biology, 2023)
Breast cancer is the most common type of cancer in women and the second cause of cancer-related death after lung cancer. Although the common methods used in the treatment of breast cancer are chemotherapy, radiotherapy and surgery, the search for alternative treatments continues. The leading alternative treatments are medicinal plants which actually inspire the production of many cancer drugs. In this study, the proliferative and metastatic effects of Carthamus tinctorius L., known for its many therapeutic properties, on metastatic breast cancer were investigated. Here, intending to evaluate the the content and actions of different extracts of safflower leaves extracts were prepared by extracting in water, alcohol and oil and analysed by FTIR. Their antioxidant effect was tested and then the extracts were applied to metastatic breast cancer cells. FTIR spectrums of all three extracts have revealed the presence of organic compounds. It is found that all extracts but mostly the oil extract has antioxidant property. MTT assay, wound healing assay and gene expression analysis were performed to assess the antiproliferative and anti metastatic effects of the extracts on breast cancer cells. It is found that, there is no significant antiproliferative effect of extracts on MDA-MB-231 cells except the alcohol extract. However, all safflower extracts, especially the oil extract, significantly reduced the metastatic potential of breast cancer cells. It is concluded that safflower contents are potent chemicals which inhibit the cellular mechanisms underlying the spreading of cancer cells and further analysis may lead to new initiatives in drug design research.